Production and characterization of a highly pure RNA polymerase holoenzyme from Mycobacterium tuberculosis - Herrera-Asmat O. (2017)
Recent publications have shown that active RNA polymerase (RNAP) from Mycobacterium tuberculosis (MtbRNAP) can be produced by expressing all four subunits in a single recombinant Escherichia coli strain [1–3]. By reducing the number of plasmids and changing the codon usage of the Mtb genes in the co-expression system published by Banerjee et al. [1], we present a simplified, detailed and reproducible protocol for the purification of recombinant MtbRNAP containing the ω subunit. Moreover, we describe the formation of ternary elongation complexes (TECs) with a short fluorescence-labeled RNA primer and DNA oligonucleotides, suitable for transcription elongation studies.